Question number 49 please find
Attachments:
![](https://hi-static.z-dn.net/files/d05/92f010fe371a351fc1adf53364dd4a86.jpg)
Answers
Answered by
3
Hi!
Here is yr answer...
= 9x² -3x -20
= 9x² - 15x + 12x -20
= 3x(3x-5) + 4(3x-5)
= (3x-5) (3x+4)
3x-5 = 0 => x = 5/3
3x+4 = 0 => x = -4/3
Hope it helps..
Here is yr answer...
= 9x² -3x -20
= 9x² - 15x + 12x -20
= 3x(3x-5) + 4(3x-5)
= (3x-5) (3x+4)
3x-5 = 0 => x = 5/3
3x+4 = 0 => x = -4/3
Hope it helps..
harsh12334:
Thanks
Similar questions
Economy,
7 months ago
Political Science,
1 year ago
Math,
1 year ago
Math,
1 year ago
Social Sciences,
1 year ago